2019
DOI: 10.24251/hicss.2019.153
|View full text |Cite
|
Sign up to set email alerts
|

Combining Enterprise Knowledge Graph and News Sentiment Analysis for Stock Price Prediction

Abstract: Many state of the art methods analyze sentiments in news to predict stock price. When predicting stock price movement, the correlation between stocks is a factor that can't be ignored because correlated stocks could cause co-movement. Traditional methods of measuring the correlation between stocks are mostly based on the similarity between corresponding stock price data, while ignoring the business relationships between companies, such as shareholding, cooperation and supply-customer relationships. To solve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 19 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…In particular, the constructed KG (named FinKG) and the implemented embeddings performs learn informative representations based on both the relations of event argument and the lead-lag relations amongst the entire KG. Liu et al [143] demonstrated the use of a KG embedding framework to predict stock prices using news sentiment analysis. Although the authors did not provide much discussion on the validity of the mechanism followed to construct the KG, the utility was demonstrated in the prediction task.…”
Section: Financementioning
confidence: 99%
“…In particular, the constructed KG (named FinKG) and the implemented embeddings performs learn informative representations based on both the relations of event argument and the lead-lag relations amongst the entire KG. Liu et al [143] demonstrated the use of a KG embedding framework to predict stock prices using news sentiment analysis. Although the authors did not provide much discussion on the validity of the mechanism followed to construct the KG, the utility was demonstrated in the prediction task.…”
Section: Financementioning
confidence: 99%
“…However, few consider inter-market or inter-company relations in the current financial market environment. Liu et al [10] comprehensively use the news sentiment as the correlation between stock companies, accompanied by stock price data, to predict the future trend. Utilizing the knowledge graph and its embedding model, they find that their method can improve significantly over baseline.…”
Section: Stock Movement Predictionmentioning
confidence: 99%
“…Despite the popularity of NLP and graph-based stock prediction, multimodal methods that capture inter stock relations and market sentiment through linguistic cues are seldom explored. Jue Liu (2019) combines feature extraction from news sentiment scores, financial information (price-earnings ratio, etc.) along with knowledge graph embeddings through TransR.…”
Section: Related Workmentioning
confidence: 99%